Transitional Cell Carcinoma in Orthotopic Ileal Neobladder - Ozgur Cakmak; Huseyin Tarhan; Orcun Celik; Ulku Kucuk; Yusuf Ozlem Ilbey (Case Reports in Urology)
Urothelial carcinoma developing in orthotopic ileal neobladder is an extremely rare entity. Fewer than 10 cases have been reported in the literature describing urothelial carcinoma recurrence in orthotopic ileal neobladder. We report a case of transitional cell carcinoma recurrence in orthotopic ileal neobladder after 11 years of surgery.